THE INFLUENCE OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) PERFORMANCE AND EARNINGS VOLATILITY ON SHARIA-COMPLIANT STOCK PRICE VOLATILITY: THE MODERATING ROLE OF LEVERAGE - Isti'anah Rizqullah; Dede Hertina (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to examine the effects of Environmental, Social, and Governance (ESG) performance and earnings volatility on Sharia-compliant stock price volatility, and to investigate the moderating role of leverage. The study employs a quantitative approach using secondary data from companies listed in the Indonesian Sharia Stock Index (ISSI) during the period 2021–2024. ESG data are derived from sustainability disclosures under the Global Reporting Initiative (GRI) Standards, while stock price volatility is measured using historical stock price data. Methods: The analysis is conducted using path analysis in SmartPLS. The results indicate that ESG performance has a negative and significant effect on Sharia-compliant stock price volatility, supporting the signaling and stakeholder perspectives that strong sustainability practices reduce perceived risk and market uncertainty (Albuquerque et al., 2020; Zhou & Zhou, 2022). Results: In contrast, earnings volatility does not have a significant effect on stock price volatility, suggesting that investors in the Islamic capital market place greater emphasis on non-financial sustainability signals than short-term earnings fluctuations (Hasanah et al., 2024). Furthermore, leverage has a significant direct effect on Sharia-compliant stock price volatility, indicating that financial risk remains a key determinant of price fluctuations. However, leverage does not moderate the relationship between ESG performance, earnings volatility, and stock price volatility. These findings contribute to the literature on Islamic capital markets by highlighting the dominant role of ESG performance in mitigating stock price volatility, while confirming the limited moderating role of leverage in the context of Sharia-compliant firms. Keywords: Environmental, Social, and Governance (ESG) Performance, Earnings Volatility, Leverage (Debt to Equity Ratio / DER), Sharia-Compliant Stock Price Volatility